Mutual funds' capital gains lock-in and earnings management - Dimmock, Stephen G. (2024)
Capital gains taxation creates a lock-in effect, increasing investors' incentives to monitor and decreasing portfolio firms' incentives to cater to short-term investors. We show a negative relation between lock-in and portfolio firms' earnings management, and this relation is stronger for capital gains held by tax-sensitive investors. Further, the relation between lock-in and earnings management is stronger when the capital gains tax rate is higher. We show that locked-in funds vote against management and against audit committee members' reappointment following earnings management. Locked-in funds are less likely to exit a position following disappointing earnings announcements, reducing firms' incentive to manage earnings.